Rush hours in flower visitors over a day–night cycle. Issue 3 (29th November 2017) - Knop, Eva; Gerpe, Christopher; Ryser, Remo; Hofmann, Fabian; Menz, Myles H. M.; Trösch, Sandra; Ursenbacher, Stefan; Zoller, Leana; Fontaine, Colin
Abstract: Most research on pollination has focussed on a subset of insect taxa within a narrow time window during daylight hours. As a consequence, we have a limited understanding of the diversity and activity of flower visitors during the night or belonging to taxa other than bees or syrphid flies. Here, we quantified the abundance and species richness of flower visitors in ruderal meadows over repeated 24‐h cycles (i.e. day and night), and identified abiotic factors influencing these patterns. From the plant perspective, we investigated the likelihood of being visited by an insect across a 24‐h cycle. Activity of flower‐visiting insects never dropped to zero over 24‐h. During the day, non‐syrphid Diptera and Hymenoptera were the most abundant, and species‐rich groups of flower visitors, Lepidoptera and Coleoptera during night. While two of the seven most frequently visited plant species were most likely to be visited during the day, five also had a high likelihood to be visited during the night. The abundance and species richness of flower visitors was positively related to temperature during both the day and the night, whereas there was only a positive relationship with brightness during the day. We conclude that non‐syrphid Diptera and nocturnal flower visitors are currently underappreciated. As the latter seem to respond differently to abiotic factors compared to diurnal species, they may potentially increase response diversity and resilience of plant‐pollinator communities. There is an urgent need to improve our understanding of their ecological role and potential decline due to global change.